2008
DOI: 10.1375/ajop.1.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Why Would You Do It? Age and Motivation to Become a Fire Service Volunteer

Abstract: Australian communities are very dependent on volunteer-based fire services for protection against fires and other hazards. However, overall volunteer numbers have declined significantly over the past decade, due mostly to the impact of economic and demographic changes on Australian society. One effect of these is that volunteer fire service memberships are ageing. Little is known with certainty about what motivates individuals to become fire service volunteers. A survey of 455 CFA volunteers suggested that tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
(2 reference statements)
0
9
1
Order By: Relevance
“…OGS are primarily mid-career medical professionals who do not have enough time to donate and are looking for a less binding form of volunteering. This finding differs from previous studies that have found that the average age of emergency services volunteers is increasing, due to sociological changes such as two-income families and longer working hours [10,73].…”
Section: Differences In the Professional Background And Demographic Ccontrasting
confidence: 99%
“…OGS are primarily mid-career medical professionals who do not have enough time to donate and are looking for a less binding form of volunteering. This finding differs from previous studies that have found that the average age of emergency services volunteers is increasing, due to sociological changes such as two-income families and longer working hours [10,73].…”
Section: Differences In the Professional Background And Demographic Ccontrasting
confidence: 99%
“…They also found that women score higher than men on all reasons to volunteer except for social motivation, on which they score similarly. Furthermore, both Francis and Jones () and McLennan and Birch () found very few intergenerational differences between the reasons to volunteer for emergency management volunteers. Both investigations found that younger (<35 years old) and more mature volunteers (>35 years old) mainly volunteered for the same reasons: “giving back to the community” and “the content of the volunteering work.” However, younger volunteers more frequently reported “career advancement” and “dealing with their own problems/emotions” as reasons to volunteer.…”
Section: Becoming a Volunteermentioning
confidence: 95%
“…Previous literature on female firefighters suggests that women experience work segregation (Yoder and Aniakudo 1997; Grube-Farrell 2002), discrimination (Hulett et al . 2008b; Branch-Smith and Pooley 2010), tokenism (Yoder and Aniakudo 1997) and sexual harassment (Mclennan and Birch 2006; Hulett et al . 2008a; Hulett et al 2008b).…”
Section: Women In Male Dominated Workmentioning
confidence: 99%
“…2008a; Hulett et al 2008b). The existing literature does well to explore the gender related discrimination occurring at both operational and auxiliary levels within specific emergency services (Mclennan and Birch 2006; Branch-Smith and Pooley 2010), however, it often fails to address how women make sense of and negotiate gender within the confines of masculinized workplaces. The lack of focus on gender negotiations in firefighting has inevitably led to a lack of deep engagement with women's ability to ‘do gender’ (West and Zimmerman 1987) within these organizations.…”
Section: Women In Male Dominated Workmentioning
confidence: 99%